2012
DOI: 10.1080/02667363.2012.669362
|View full text |Cite
|
Sign up to set email alerts
|

Narrative therapy with an adolescent who self-cuts: a case example

Abstract: identifies educational psychologists as appropriate specialists to deliver interventions to promote the emotional well-being of children and families. A role for practitioner educational psychologists in providing specific therapeutic interventions has also been proposed by commentators. The present study reports an evaluative case study of a narrative therapy intervention with a young person who self-harms. The analysis of data suggests that the narrative therapy intervention was effectively implemented and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…All of the studies identified at least some positive impacts resulting from the therapeutic intervention. Eight reported favorable social/ emotional outcomes, such as increased optimism and improved self-concept (Ardern, 2016;Cole et al, 2012;Hannen & Woods, 2012;Kittles & Atkinson, 2009;Squires & Caddick, 2012;Weeks, Hill & Owen, 2017;Yates & Atkinson, 2011;Yeo & Choi, 2011). Four reported academic gains, such as improvements in reading skills (Bosnjak et al, 2017;Chodkiewicz & Boyle, 2016, Cockroft & Atkinson, 2017Toland & Boyle, 2008) and four identified improvements in behavioral measures, such as academic enabling behaviors (Briesch DuBois et al, 2017;Cryer & Atkinson, 2015;Levine & Anshel, 2011;Snape & Atkinson, 2017).…”
Section: Impact Of Therapeutic Interventionsmentioning
confidence: 99%
“…All of the studies identified at least some positive impacts resulting from the therapeutic intervention. Eight reported favorable social/ emotional outcomes, such as increased optimism and improved self-concept (Ardern, 2016;Cole et al, 2012;Hannen & Woods, 2012;Kittles & Atkinson, 2009;Squires & Caddick, 2012;Weeks, Hill & Owen, 2017;Yates & Atkinson, 2011;Yeo & Choi, 2011). Four reported academic gains, such as improvements in reading skills (Bosnjak et al, 2017;Chodkiewicz & Boyle, 2016, Cockroft & Atkinson, 2017Toland & Boyle, 2008) and four identified improvements in behavioral measures, such as academic enabling behaviors (Briesch DuBois et al, 2017;Cryer & Atkinson, 2015;Levine & Anshel, 2011;Snape & Atkinson, 2017).…”
Section: Impact Of Therapeutic Interventionsmentioning
confidence: 99%
“…Researchers have demonstrated the clinical effectiveness of narrative therapy for both individual counseling (Bucellato, ; Cashin, Browne, Bradbury, & Mulder, ; Hannen & Woods, ; Matthes‐Loy, ) and group counseling formats. Specifically, they found the narrative group approach successful with women with depression and eating disorders (Weber, Davis, & McPhie, ) and children with learning disabilities, depression, oppositional defiant disorder (Sheibani, Yoosefi Looyeh, & Delavar, ; Yoosefi Looyeh, Kamali, & Ashrafpouri, in press; Yoosefi Looyeh & Matin, ), and ADHD (Hill, ).…”
Section: Narrative Therapy and Women With Adhdmentioning
confidence: 99%
“…The first is narrative therapy (NT), in which the student ''writes to the problem,'' allowing it to be externalized and therefore managed (Hoffman & Kress, 2008). Hannen and Woods (2012) presented a case study examining the use of NT with a 12-year-old girl who self-cut. Narrative therapy involved strategies such as externalizing (e.g., ''I cut when I am angry, but I am only angry some of the time''), reauthoring (e.g., ''I will refer to my challenge as 'moving towards independence'''), and re-membering (e.g., ''I will talk about who will be supportive to me'').…”
Section: Tier 2: Clinical Therapy and Function-based Strategiesmentioning
confidence: 99%